EKSOTISME DAN IDENTITAS ISLAM DALAM SASTRA KONTEMPORER INDIA DAN PAKISTAN - Risma Fadilla; Silva Saputri; Nurholis Nurholis (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
Abstract Exoticism is an important concept in literature, especially in works that depict cultures foreign to their readers. This article explores exoticism in three literary works set in India and Pakistan: The Holy Woman and Typhoon by Qaisra Shahraz, as well as Taj Mahal by John Shors and Taj by Timeri N. Murari. Through a comparative approach, this article analyzes how exoticism functions not only as an aesthetic appeal, but also as a tool to critique social norms. Qaisra Shahraz utilizes exoticism to highlight the injustice of patriarchy in Pakistan, while John Shors and Timeri N. Murari use the historical and architectural exoticism of the Taj Mahal to present a romantic and intriguing narrative. The results of this study show that exoticism in literature can enrich the understanding of other cultures, as well as being an effective medium for social criticism. Keywords: exoticism, literature, India, Pakistan, patriarchy, Taj Mahal. Abstrak Eksotisme adalah konsep penting dalam sastra, terutama dalam karya yang menggambarkan budaya asing bagi pembacanya. Artikel ini mengeksplorasi eksotisme dalam tiga karya sastra yang berlatar India dan Pakistan: The Holy Woman dan Typhoon oleh Qaisra Shahraz, serta Taj Mahal oleh John Shors dan Taj oleh Timeri N. Murari. Melalui pendekatan komparatif, artikel ini menganalisis bagaimana eksotisme tidak hanya berfungsi sebagai daya tarik estetis, tetapi juga sebagai alat untuk mengkritik norma sosial. Qaisra Shahraz memanfaatkan eksotisme untuk menyoroti ketidakadilan patriarki di Pakistan, sementara John Shors dan Timeri N. Murari menggunakan eksotisme sejarah dan arsitektur Taj Mahal untuk menyajikan narasi romantis dan penuh intrik. Hasil kajian ini menunjukkan bahwa eksotisme dalam karya sastra dapat memperkaya pemahaman tentang budaya lain, sekaligus menjadi media kritik sosial yang efektif. Kata kunci: eksotisme, sastra, India, Pakistan, patriarki, Taj Mahal.